Epistemologia, metodologia e prática de um modelo cartográfico de avaliação curricular em educação médica - Lira, Geison Vasconcelos (2010)
The call for change in Medical Education highlights the curriculum as a central dimension of practice, demanding from evaluators to demonstrate the effectiveness of new curricula. The critical review of international literature in order to analyze the present status of curriculum evaluation research demonstrated that it is reductionist in curriculum interpretation as scientific subject, superficial in its theoretical framework, and oversimplified in its method. In order to deal with the aim of developing an evaluation model capable to catch the medical curriculum change processes and its complexity, it was did a methodological inquiry covering the epistemological, theoretical, morphological and technical dimensions in Social Sciences, and the pragmatic of scientific research. The inquiry on epistemological dimension formulated a critical and postmodern curriculum evaluation paradigm that can be an antidote to the factory metaphor, the most persistent verbal epistemological obstacle to the scientific development of Evaluation. The inquiry on theoretical dimension highlights the hole of postmodern critical theory and of theoretical bricolage in curriculum evaluation. The inquiry in morphological dimension permitted to propose a cartographic model of medical curriculum evaluation having, as scales, the external, internal and personal levels; as projections, the agents, beneficiaries and victims; and, as symbolic processes, power, epistemological and pedagogical dimensions. It was demonstrated that the model attended the curriculum theory requirements. The inquiry on technical dimension was done due a case study, where the model main categories were empirically explored. The evidences gathered show their heuristic power towards medical curriculum complexity. The bricolage feedback of the model by the empirical data permitted to incorporate new categories to it. In conclusion, it was sustained the thesis that the evaluation of curriculum implantation and curriculum change processes in the social and historical context of late capitalism, and of the complexity of curriculum as educational subject, have to be related to a methodological conception of Evaluation founded in the critical theory paradigm reconfigured in a postmodern context. New research directions were defined aiming to improve the cartographic model of curriculum evaluation.